Extracellular vesicles and a novel form of communication in the brain - Manuela eBasso; Valentina eBonetto (Frontiers in Neuroscience, 2016)
In numerous neurodegenerative diseases, the interplay between neurons and glia modulates the outcome and progression of pathology. One particularly intriguing mode of interaction between neurons, astrocytes, microglia, and oligodendrocytes is characterized by the release of extracellular vesicles that transport proteins, lipids, and nucleotides from one cell to another. Notably, several proteins that cause disease, including the prion protein and mutant SOD1, have been detected in glia-derived extracellular vesicles and observed to fuse with neurons and trigger pathology in vitro. Here we review the structural and functional characterization of such extracellular vesicles in neuron-glia interactions. Furthermore, we discuss possible mechanisms of extracellular vesicle biogenesis and release from activated glia and microglia, and their effects on neurons. Given that exosomes, the smallest type of extracellular vesicles, have been reported to recognize specific cellular populations and act as carriers of very specialized cargo, a thorough analysis of these vesicles may aid in their engineering in vitro and targeted delivery in vivo, opening opportunities for therapeutics.